An Investigation of the Changes in the Iran Precipitation Extreme Indices in Two Normal Climate Periods, 1981-2010 and 2020-1991 - Zohreh Javanshiri; Ebrahim Asadi Oskouei; Fatemeh Abbasi (Nīvār)
Precipitation fluctuation is a critical factor in understanding climate, as it has far-reaching impacts on the environment, economy, and society. Excessive or insufficient precipitation can result in severe floods and droughts, causing significant consequences for both nature and humanity. For this reason, it is vital to understand the variability, behavioral changes, and extreme precipitation levels to successfully manage industries like agriculture, water resources, urban planning, and transportation. In this study, to investigate the extreme values of precipitation, the trends of four precipitation indices of 44 synoptic stations in Iran were calculated and compared for two recent climate normal periods of 1981-2010 and 1991-2020. Four precipitation indices, specifically PRCPTOT95, PRCPTOT99, R10MM, and R20MM, were investigated after undergoing quality control and data homogenization. An evaluation of the trend of heavy precipitation in two periods demonstrated a decrease in the eastern and northwestern parts of the country, while an increase was observed in the Zagros and northern regions. The increasing trend in the second period has become more significant in the northern part of the country, while the decreasing trend in the western part has decreased in the second period. The analysis of mean precipitation indices in two periods showed that heavy precipitation had increased in the second period on the coasts of the Caspian Sea, Zagros Mountains, and southern parts and decreased in the east of Iran.